Deep level study of beryllium implanted MOCVD homoepitaxial GaN. (12th April 2019) - Alfieri, G.; Sundaramoorthy, V. K.
Abstract: We present the electrical characterization of point defects detected in beryllium implanted GaN epilayers. We found six majority carrier traps, in the 0.2–1.2 eV energy range below the conduction band edge. An isochronal annealing study was carried out in order to investigate the thermal stability of the detected levels. Most of these possess a high thermal stability up to 1273 K. Their microscopic structures are discussed in the light of the present experimental data and previous reports found in the literature.